Perubahan Struktur Tenaga Kerja Indonesia Akibat Penerapan Artificial Intelligence dalam Konteks Budaya Kerja Masyarakat Indonesia - Syosti Sara, Ni Komang Yasoda; Yanti, Putu Dea Anggita; Sidaryanti, Ni Nyoman Asri; Balakrishnan, Vishalache; Mahendra, Ngakan Putu Yoga Aditya; Dewi, Putu Purnama; Putri, Saskia Adya; Maharani, Kunti Afrida (Ganesha Civic Education Journal, 2025)
The development of Artificial Intelligence (AI) technology has had a significant impact on the structure of the workforce, including in Indonesia. This study examines the implications of AI implementation on changes in the national workforce structure and the transformation of traditional work culture values such as family values, loyalty, and hierarchy. The method used is qualitative descriptive through a literature review of academic literature from the past five years. The study covers shifts in work roles, changes in organizational culture values, and adaptive responses from society and institutions to digitalization. The results indicate that while AI enhances efficiency and productivity, the automation of routine tasks particularly in manufacturing and customer service sectors may reduce the need for conventional labor and drive demand for new competencies such as digital literacy, data analysis, creativity, and emotional intelligence. Therefore, adaptive collaboration between government, industry, and educational institutions is needed to formulate inclusive training policies and organizational cultural adaptation strategies to support the readiness of the national workforce to face digital transformation in a fair and sustainable manner.